2017
DOI: 10.1002/jbm.a.36099
|View full text |Cite
|
Sign up to set email alerts
|

Polytetrafluoroethylene topographies determine the adhesion, activation, and foreign body giant cell formation of macrophages

Abstract: Polytetrafluoroethylene (PTFE) is one of the commonly used materials in making various cardiovascular implants. However, the success rates of these implants in several occasions are hindered by unwanted immune responses from immune cells, such as macrophages. In this study, we investigated the response of macrophages with different structures (flat, expanded, and electrospun) of PTFE having varied surface topographies: smooth planar surface (flat PTFE), node-fibrils (ePTFE), and randomly oriented microfibers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 42 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…The authors argue that cell adhesion to the material was hampered due to spatial limitations, reduced cell‐material contact area, and a curvature threshold effect . They also demonstrated that topographical/geometrical (suture) features, such as a small inter‐filament distance (<8 μm), prevents macrophage adhesion. Furthermore, Saino et al stated that adhesion of macrophages and their expression of proinflammatory cytokines/chemokines were mainly dependent on filament diameter.…”
Section: Discussionmentioning
confidence: 97%
“…The authors argue that cell adhesion to the material was hampered due to spatial limitations, reduced cell‐material contact area, and a curvature threshold effect . They also demonstrated that topographical/geometrical (suture) features, such as a small inter‐filament distance (<8 μm), prevents macrophage adhesion. Furthermore, Saino et al stated that adhesion of macrophages and their expression of proinflammatory cytokines/chemokines were mainly dependent on filament diameter.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been shown that nearly every biomaterial induces an inflammatory tissue reaction, which is unique for every material depending on its combination of physical and chemical properties [ 15 ]. This tissue reaction to a biomaterial is a cascade including mainly macrophages as key elements, which have been shown to express both pro- and anti-inflammatory molecules depending on material factors such as surface topography or surface chemistry [ 16 , 17 , 18 ]. Based on their molecule expression, macrophages are more or less divided into pro-inflammatory M1- and anti-inflammatory M2 subtypes [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages (and also BMGCs) have been shown to express both pro-and anti-inflammatory molecules, depending on material factors such as surface topography or surface chemistry (33)(34)(35). Based on the expression of certain molecular markers, macrophages are more or less divided into pro-inflammatory M1-and anti-inflammatory M2 subtypes (36,37).…”
mentioning
confidence: 99%